Manajemen Pembelajaran Bahasa Inggris Melalui Kegiatan Ekstrakurikuler untuk Mengembangkan Retorika Siswa Di SLTA: Studi Deskriptif Di SMA IT dan SMK Bani Masum Cisalak Kabupaten Subang - Faisal Abda’u; Iim Wasliman; Cahya Syaodih (Universitas Nusantara PGRI Kediri, 2022)
This study aims to obtain data, explore and analyze the management of the English language extracurricular learning process to develop student rhetoric which includes planning, organizing, implementing, evaluating, problems and efforts to improve them. This research was conducted in SMA and SMK Bani Masum Subang district with a qualitative approach and descriptive study method. The research technique used is observation, interview and documentation study. The results of this study indicate that the management of the learning process through English extracurricular activities to improve students' rhetoric, namely: 1) Planning has been carried out but in planning this planning is carried out personally and has not referred to applicable guidelines. 2) Organizing has been carried out and regulated by the teacher even though the organization is still not in accordance with the guidelines but has led to the applicable guidelines. In the process of learning English, giving a larger portion in the speaking aspect is a correct guideline, but in this study the results showed that the portion for the speaking aspect was still small. 3) Implementation has been in accordance with the plans that have been made, but there are still plans that have not been implemented properly such as the unrealized use of methods, media and the presence of teachers in class. 4) Evaluation has been carried out but there is little feedback in the next learning process. 5) problems that occur come from internal and external schools. 6) Improvement efforts have been carried out properly, one of which is by involving teachers in the regional English community, schools provide upgrades to teachers such as English language training and are given the authority to explore English learning management in extracurricular activities. The impact of the implementation of English extracurricular learning management to develop students' rhetoric is the creation of students who have active language skills properly and correctly.